Customer Loyalty in Fast-Food Restaurants: The Mediating Role of Customer Satisfaction in Batam - Mohamad Gita Indrawan; Angelina Eleonora Rumengan; Raymond Raymond (Annals of Management and Organization Research, 2026)
Purpose:  This study aims to examine the direct and indirect effects of selling price, advertising, and location on customer loyalty, with service quality acting as a mediating variable in fast food outlets in Batam City. Methodology: This study employed a quantitative approach using a survey method. Data were collected from customers who purchased and consumed fast-food products in Batam City. The sampling technique used was purposive sampling, and the data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to test both direct and indirect relationships among variables. Results: The findings indicate that selling price significantly affects service quality but does not directly influence customer loyalty, demonstrating a full mediating effect through service quality. Advertising and location have significant direct and indirect effects on customer loyalty, indicating partial mediation. Furthermore, service quality significantly affects customer loyalty and is the most critical determinant of customer retention. Conclusions:   This study confirms that service quality is a key mechanism linking marketing variables to customer loyalty. The effectiveness of pricing, advertising, and location strategies largely depends on their ability to enhance the perceived service quality. Limitations:  This study is limited to fast-food outlets in Batam City and focuses only on selected variables, which may restrict the generalizability of the findings to other regions. Additionally, the cross-sectional design does not capture changes in customer behavior over time. Contributions:  This study contributes to the literature by integrating marketing mix variables with service quality within the Stimulus-Organism-Response (S-O-R) framework, highlighting the mediating role of service quality in shaping customer loyalty. Practically, it provides insights for fast-food businesses to align their marketing strategies with service quality improvements to achieve a sustainable competitive advantage.